2013
DOI: 10.1111/sji.12056
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Induces Activated T Cell Apoptosis Through Reduced T Cell Receptor

Abstract: Glucosamine (GlcN), like N-acetylglucosamine (GlcNAc), is salvaged into the hexosamine pathway and is converted to UDP-GlcNAc. Golgi N-glycan branching enzymes produce N-glycans, using UDP-GlcNAc as a substrate, which attach to the T cell receptor (TCR) and cytotoxic T-lymphocyte antigen-4 (CTLA-4). These findings suggest that GlcN exerts the immunoregulation through TCR signalling, which could be involved not only in cytokine production but also activated T cell apoptosis. In fact, a preliminary study showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Glucosamine can be recovered in the hexosamine pathway and converted to UDP-GlcNAc. Using UDP-GlcNAc as a substrate, golgi N-glycan branching enzymes produce N-glycans, which bind to the T-cell receptor (TCR) and cytotoxic T lymphocyte antigen-4 (CTLA-4), indicating that glucosamine can regulate autoimmunity by modulating the multiple functionalities of T cells and suggesting that it exerts immunoregulation through TCR signaling, increasing the number of T cells (Chen et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Glucosamine can be recovered in the hexosamine pathway and converted to UDP-GlcNAc. Using UDP-GlcNAc as a substrate, golgi N-glycan branching enzymes produce N-glycans, which bind to the T-cell receptor (TCR) and cytotoxic T lymphocyte antigen-4 (CTLA-4), indicating that glucosamine can regulate autoimmunity by modulating the multiple functionalities of T cells and suggesting that it exerts immunoregulation through TCR signaling, increasing the number of T cells (Chen et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Glucosamine (GlcN) is salvaged into the hexosamine pathway [ 25 ]. It suppresses T cell function by increasing the apoptosis of activated T cells [ 26 ]; urolithin treatment induces glucosamine accumulation in leukemic cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was worth noting that there were a few reports on the qualitative and quantitative analysis for the composition changes in the prepared slices of Yinyanghuo compared to raw products. The content of aglycones and secondary glycosides of flavonoids in Yinyanghuo increased due to the desugarization reactions in frying (Jing et al, 2009), and it was confirmed by some studies that the content of epimedin A, B and C decreased, while icariin increased when the herb was processed (Xie et al, 2011;Chen and Luo, 2013;Zhang et al, 2018;XU et al, 2021). And the increased icariin was proved to be a hydrolysis product of 3´´´-carbonyl-2´´-β-L-quinovosyl icariin instead of epimedin A, B and C (Sun et al, 2018).…”
Section: The Composition Changes Of Pfeb and Rfeb And The Future Pros...mentioning
confidence: 88%